2013
DOI: 10.1074/jbc.m112.406462
|View full text |Cite
|
Sign up to set email alerts
|

βIII Spectrin Regulates the Structural Integrity and the Secretory Protein Transport of the Golgi Complex

Abstract: Background: ␤III spectrin function at the Golgi remains unclear. Results: ␤III spectrin is enriched in distal Golgi compartments and supports anterograde transport. PI4P is determinant for the ␤III spectrin association with Golgi membranes. Conclusion: ␤III spectrin is necessary for the structural and functional organization of the Golgi. Significance: We provide new in vivo insights of the role of ␤III spectrin at the Golgi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Cofilin is associated with the TGN, and plays a role in cargo sorting[118, 119]. There is also suggestion of a spectrin-actin meshwork at or close to the Golgi, with its integrity affecting Golgi function[108, 120, 121]. Finally, multiple myosins (in the I, II, VI and XVIII families) play roles in Golgi structure/function[113, 117, 122].…”
Section: Golgimentioning
confidence: 99%
See 2 more Smart Citations
“…Cofilin is associated with the TGN, and plays a role in cargo sorting[118, 119]. There is also suggestion of a spectrin-actin meshwork at or close to the Golgi, with its integrity affecting Golgi function[108, 120, 121]. Finally, multiple myosins (in the I, II, VI and XVIII families) play roles in Golgi structure/function[113, 117, 122].…”
Section: Golgimentioning
confidence: 99%
“…Two issues should be raised here. First, these proteins often “enrich” at Golgi, but are also abundant in vesicular structures surrounding Golgi or elsewhere[115, 121]. Sometimes, the proteins shown to affect Golgi structure have little or no actual enrichment there[110, 111].…”
Section: Golgimentioning
confidence: 99%
See 1 more Smart Citation
“…Using a spectrin III subunit containing the green fluorescent protein tag in transfected COS cells, spectrin decorated the tubular-vesicular transport intermediates moving along microtubules between the endoplasmic reticulum and the Golgi apparatus, requiring the participation of the MAD1 domain [45]. Salcedo-Sicilia et al [46] suggested that III spectrin helps to maintain the structural integrity and secretory activity of the Golgi complex by associating with phosphatidylinositol 4-phosphate (PI4P).…”
Section: Spectrin and Intracellular Trafficmentioning
confidence: 99%
“…It is known that at a short pulse duration accumulation of radicals and active particles in the substrate runs slower [4] and, therefore, erythrocytes also hemolyze slower in such situation, and a greater quantity of cells retain the viability. A protein cytoskeleton of erythrocytes responsible for elasticity and integrity of the membrane [12] is subjected to destructive changes to the greater extent after exposure to spark discharge plasma with 1,500 μs pulse duration and ultraviolet radiation of the mercury lamp.…”
mentioning
confidence: 99%